Creation of a State Drug Shortage Dashboard in the COVID-19 Pandemic. (August 2022) - Lux, Kristin; Jorns, Melinda; Vogler, Carrie
Purpose: Drug shortages are anticipated to worsen with time as the Coronavirus Disease 2019 (COVID-19) pandemic continues. The aim of this study is to track drug shortages within Illinois and identify causes and trends to this time-sensitive problem.Methods: In order to communicate between health systems within the state, the Illinois Council of Health-System Pharmacists (ICHP) developed a medication shortage dashboard, which collects information from health systems in the state on current drug shortages. Classes of medications inquired about included: anti-infectives, neuromuscular blocking agents (NMBAs), sedatives/analgesics, vasopressors, and "others." Data was gathered from 6 different medication shortage dashboards, ranging from May 20, 2020 to June 22, 2020 and was used to track drug shortages within Illinois. Additionally, this data was analyzed in conjunction with the number of hospital beds utilized by COVID-19 patients at the time.Results: Illinois's medication shortage dashboard tracked the supply level of 42 medications used in the treatment of patient's hospitalized with COVID-19. Data from an average of 75 health systems was analyzed each week (average response rate: 52%). For each medication, health systems identified if they had ample supply, mild shortage, moderate shortage, or critical shortage. Overall the trends of these medications positively correlated with the number of hospital beds utilized by COVID-19 patients in Illinois ( r 2  = 0.7).Conclusion: The data from this study supports the conclusion that increased hospital bed utilization by COVID-19 patients is correlated with increased drug shortages of medications used in the treatment of COVID-19. It is imperative that health systems take appropriate action to prevent and manage drug shortages.